Establishment and performance analysis of RIS-assisted coded relay cooperation system based on LDPC product codes - Shunwai ZHANG; Jin WANG (Tongxin xuebao)
To pursue the ultra-reliable information transmission, the system which combined the reconfigurable intelligent surface (RIS) technology and coded relay cooperation technology was investigated.The RIS-assisted coded relay cooperation system model based on low density parity check (LDPC) product codes was established.Based on LDPC product codes, the information matrix was row-encoded by the source node and column-encoded by the relay node, respectively.An efficient joint iterative decoding algorithm was proposed.The two received signals at the destination were row-decoded and column-decoded iteratively to update the logarithmic likelihood ratios of information bits, and then the decoding decision was made.The closed-form solutions of the outage probability and the channel capacity with finite codelength were theoretically derived.Theoretical analysis and simulation results show that the proposed system obviously outperforms the traditional coded relay cooperation.The more number of RIS elements, the more significant advantage can be obtained.Simulation results also demonstrate that the channel capacity with finite codelength approaches the ideal channel capacity with the codelength of LDPC product codes increasing.